A Comparison of Competences for Healthcare Professions in Europe - Antonio Sánchez-Pozo (MDPI AG, 2017)
In Europe and elsewhere, there is increasing interest in competence-based education (CBE) and training for professional practice in healthcare. This review presents competences for pharmacy practice in Europe and compares them with those for medicine and dentistry. Comparisons amongst competence frameworks were made by matching the European Directive for Professional Qualifications in sectoral professions such as healthcare (EU directive) with the frameworks of competences elaborated by European consortia in pharmacy (PHAR-QA), medicine (MEDINE), and dentistry (ADEE). The results show that the recommendations of the EU directive for all three professions are similar. There is also widespread similarity in the formulation of competences for all healthcare professions. Furthermore, for medicine and pharmacy, the rankings by practitioners of the vast majority of competences are similar. These results lay the foundations for the design of more interdisciplinary educational programs for healthcare professionals, and for the development of team-based care.